Evaluating the Impact of Digital Services Tax on Compliance and Economic Equity - Anggraeni, Rasmi Nur (Sinergi International Journal of Accounting and Taxation, 2024)
The rapid digitalization of economies worldwide has posed significant challenges to traditional tax systems, necessitating the development of digital taxation policies such as the Digital Services Tax (DST) and electronic levy (E-levy). This study systematically reviews the effectiveness and limitations of digital tax frameworks, analyzing their impact on tax compliance, economic equity, and revenue generation. Using Scopus, Google Scholar, and PubMed, relevant literature was assessed based on empirical findings, regulatory analysis, and socio-economic implications. The findings indicate that while digital tax policies have contributed to increased government revenues, their implementation varies widely across regions. Countries with clear and structured regulatory approaches have achieved higher compliance rates, whereas developing economies often struggle with enforcement due to inadequate digital infrastructure and public resistance. Moreover, the review highlights concerns about fairness, particularly in taxing the informal sector and digital small enterprises, emphasizing the need for improved tax literacy and transparent policy frameworks. This study concludes that digital taxation must balance revenue generation with social equity to ensure long-term sustainability. Future research should explore technological solutions such as blockchain and AI to enhance efficiency and compliance. Policymakers must design adaptable tax strategies that accommodate evolving digital markets while ensuring economic inclusivity and fairness.